Identification of Ectoparasites in Snakehead Fish (Channa striata) in Sebangau River Palangka Raya Central Kalimantan - Ide Refika BR Sembiring; Maryani Maryani; Shinta S Monalisa; Toto Fransisco (Universitas Batangahari Jambi, 2021)
The study aimed at identifying the types of parasites that infect snakehead (Channa striata) fish as well as to determine the prevalence of the parasite species then examined at Parasitology Laboratory of Fish Quarantine Station Quality Control and Safety of Fishery Products in Palangka Raya to see the presence of ectoparasites in snakehead fish. Examination of ectoparasites is done by observing the external organs and by making a mucus smear which is examined under a microscope. From the results of the study found 3 types of parasites that infest snakehead fish in the Sebangau River, Palangka Raya, namely Dactyloyrus sp, Henneguya sp, Trichodina sp. The most common ectoparasites that attack the gills of snakehead fish are Dactylogyrus sp with a prevalence of 70% and an intensity of 2.14 cells/ind, Henneguya sp with a prevalence of 20% and an intensity of 7.68 cells/ind, and Trichodina sp with a prevalence of 10% and an intensity of 4.29.